2017
DOI: 10.1159/000477933
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk to Develop Preeclampsia in the First Trimester Combining Promoter Variant -98A/C of LGALS13 (Placental Protein 13), Black Ethnicity, Previous Preeclampsia, Obesity, and Maternal Age

Abstract: Background:LGALS13 (placental protein 13 [PP13]) promoter DNA polymorphisms was evaluated in predicting preeclampsia (PE), given PP13's effects on hypotension, angiogenesis, and immune tolerance. Methods: First-trimester plasma samples (49 term and 18 intermediate) of PE cases matched with 196 controls were collected from King's College Hospital, London, repository. Cell-free DNA was extracted and the LGALS13 exons were sequenced after PCR amplification. Expression of LGALS13 promoter reporter constructs was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“… 5 PP13 serum levels in these women vanished very slowly after delivery and could be determined for 5–6 weeks postpartum and occasionally longer. 5 A recent study by Madar-Sharipo et al 36 has shown that combining the presence of the A/A genotype in the −98 site of the PP13 promoter with obesity, African (black) origin, and history of preeclampsia significantly increases the accuracy of predicting the risk of preeclampsia. 28 The determination of low serum levels of PP13 in early pregnancy contributes to the prediction of preeclampsia as well.…”
Section: Discussionmentioning
confidence: 99%
“… 5 PP13 serum levels in these women vanished very slowly after delivery and could be determined for 5–6 weeks postpartum and occasionally longer. 5 A recent study by Madar-Sharipo et al 36 has shown that combining the presence of the A/A genotype in the −98 site of the PP13 promoter with obesity, African (black) origin, and history of preeclampsia significantly increases the accuracy of predicting the risk of preeclampsia. 28 The determination of low serum levels of PP13 in early pregnancy contributes to the prediction of preeclampsia as well.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these galectins is dependent on trophoblast differentiation, and this developmentally regulated process in the trophoblast emerged during primate evolution (110). Of importance, Gal-13 is secreted from the syncytiotrophoblast into the maternal circulation, and low Gal-13 concentration in the maternal circulation in the first trimester was found in women who subsequently developed preterm preeclampsia (115122), a severe obstetrical syndrome with a strong systemic immune dysregulation (51, 82, 86, 123128) that already exists in the first trimester (129). Our studies have also shown that the placental expression of Gal-13 and Gal-14 is down-regulated in preterm preeclampsia (81, 110, 113, 129), where the placental pathology and the pro-inflammatory changes are similar to that of miscarriage (130135).…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Hans Bohn was one of the most eminent scientists of the field, who purified more than 50 proteins from the human placenta, which he named sequentially, and generated highly specific antibodies against them (Than, Bohn & Szabo, 1993). Later studies showed that many of the so-called soluble PPs secreted from the placenta into the maternal circulation, such as Placental Protein 5 (PP5, tissue factor pathway inhibitor-2, TFPI-2) or Placental Protein 13 (PP13, galectin-13), have important roles in placental functions and diagnostic significance in pregnancy complications (Than et al, 1999, 2004, 2008, 2011, 2014a, 2014b, 2018; Visegrady et al, 2001; Romero et al, 2008; Balogh et al, 2011; Madar-Shapiro et al, 2018; Karaszi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%